2010
DOI: 10.3389/fneur.2010.00125
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Complaints Affecting School Performance at Different Educational Levels

Abstract: The clear association between reports of sleep disturbance and poor school performance has been documented for sleepy adolescents. This study extends that research to students outside the adolescent age grouping in an associated school setting (98 middle school students, 67 high school students, and 64 college students). Reported restless legs and periodic limb movements are significantly associated with lower GPA's in junior high students. Consistent with previous studies, daytime sleepiness was the sleep var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 31 publications
(54 reference statements)
4
43
1
2
Order By: Relevance
“…This finding among our pharmacy students is consistent with findings from other studies on undergraduate college students, medical students, and nursing students. 6,8,[10][11][12][13][14]18 Strengths of the study included a large sample size with a satisfactory response rate, use of a standardized measure of sleep quality, and careful selection of an administration date that minimized a potential confounding variable across class cohorts. However, there were limitations as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding among our pharmacy students is consistent with findings from other studies on undergraduate college students, medical students, and nursing students. 6,8,[10][11][12][13][14]18 Strengths of the study included a large sample size with a satisfactory response rate, use of a standardized measure of sleep quality, and careful selection of an administration date that minimized a potential confounding variable across class cohorts. However, there were limitations as well.…”
Section: Discussionmentioning
confidence: 99%
“…9 Studies have found a correlation between sleep disturbances and decreased academic performance in college students. 6,8,10,11 Various studies have examined the sleep of medical, nursing, and pharmacy students. Sleep difficulties have been reported among Saudi Arabian, Brazilian, and Estonian medical students, and were associated with decreased academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…It was found from various studies done in different countries that academic performance of medical students and health status were affected by sleep deprivation. 7,8 No such data regarding the same is available in Tripura. Therefore the present study was aimed to find out the magnitude of sleep disturbance and its effect on academic performance of medical students in a Medical College & Hospital of Tripura.…”
Section: Introductionmentioning
confidence: 99%
“…19 Similar were the results of other studies on behavior and academic performance. 20,21 The major limitation of the study is only academic performance in Community Medicine is assessed. Therefore, it cannot be generalized to the entire MBBS course.…”
Section: Discussionmentioning
confidence: 99%